Adaptation of the social media burnout scale: a validity and reliability study - Gündoğan, Selim (Journal of Dependence, 2022)
Objective: The aim of this study is to adapt the social media burnout scale (SMBS) to Turkish culture. Method: This study is a scale adaptation study. The data of the study were collected from individuals who continued their high school or university education. The participant group of the study consisted of a total of 499 individuals, 282 girls (57%) and 217 boys (43%), whose age range was between 14 and 22, reached by the convenient sampling method. Results: In order to determine the language validity of the SMBS, the Turkish and English forms of the scale were applied to the individuals who are fluent in both languages, and it was found to have language validity. Confirmatory factor analysis (CFA) was applied to test construct validity. As a result of CFA, both level 1 and level 2 CFA fit indices met the criteria. In order to test the criterion validity of SMBS, the relationship between social media disorder scale was examined, and positive significant relationships were found between the two scales. The reliability of the SMBS was examined with internal consistency, split half, and test-retest. All three values met the desired criteria. Conclusion: It was concluded that the SMBS adapted in this study is a reliable and valid measurement tool that can be used in Turkish culture.